Dysregulation of bile acids increases the risk for preterm birth in pregnant women - Sangmin You (Nature Portfolio, 2020)
Preterm birth (PTB) is the leading cause of perinatal mortality and newborn complications with limited treatment options. Here the authors show that dysregulation of bile acids increases risk for PTB in pregnant women while restoring bile acid homeostasis delays or prevents PTB in the mouse models.